Potential efficacy of Coenzyme Q10 against oxytetracycline-induced hepatorenal and reproductive toxicity in male rats - Samah S. Oda, Reham S. Waheeb, Zeynab Kh. El-Maddawy (Journal of Applied Pharmaceutical Science, 2018)
This study was performed to assess potential efficacy of Coenzyme Q10 (CoQ10) to restore oxytetracycline (OXT)-in¬duced toxicity. Rats were distributed into four equal groups (6 each). The Control group received propylene glycol (0.5 ml p.o). CoQ10 group received Coenzyme Q10 (10 mg/kg BW p.o). OXT group (rats were injected intraperitoneally with 200 mg/kg BW oxytetracycline hydrochloride). OXT+CoQ10 group (rats were given the combined treatments). Treatments were used daily for seven days. Results indicated that OXT induced significant changes in serum biochem¬ical parameters, significant increase of lipid peroxidation and exhaustion of reduced glutathione and catalase in liver, kidney and testis. Also, OXT reduced serum testosterone levels besides sperm motility and viability. Histopathological changes were marked in liver, kidney and to some extent in testis and epididymis. CoQ10 treatment restored oxidative stress in liver, kidney and testis, improved serum testosterone levels, sperm motility/viability as well as histopatholog¬ical alterations. In conclusion, short-term administration of OXT induced hepatorenal and male reproductive toxicity through oxidative stress. This study is the first to suggest that CoQ10 could provide partial protection against OXT-in¬duced hepatorenal/reproductive toxicity in male rats.
Keywords: Coenzyme Q10,Oxytetra¬cycline,Oxidative stress,Histopathology,Semen quality.